Analysis of Similarities in Principle and Resolution Between MS Glow and PS Glow Brand Disputes - Aulia Kintamani, Risalatul Putri; Wins, Basoeky (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This research discusses similarities in essence as regulated in Article 6 paragraph (1) letter b of Law No. 15 of 2001 concerning Trademarks in its explanation regarding the rejection of applications that have similarities in overall terms and conditions of similar goods and services but are detrimental to well-known brands. In this legal research, normative and secondary research is used, including primary legal materials and secondary legal materials. The technique of collecting legal materials is carried out by the literature and then analysis techniques are used. The results showed that it is already familiar to the public and the resolution of disputes experienced by the MS GLOW and PSGlow brands is reviewed from Law No. 20 of 2016 concerning Marks and Geographical Indications.